A Rare Cause of Sleep-Disordered Breathing: ROHHAD Syndrome - Özcan, Gizem; Özsu, Elif; Şiklar, Zeynep; Çobanoğlu, Nazan (Frontiers in Pediatrics, 2020)
Rapid-onset obesity with hypoventilation, hypothalamic dysfunction and autonomic dysregulation (ROHHAD) syndrome; is rare. Sleep-disordered breathing, both obstructive sleep apnea and central hypoventilation, can occur at the beginning or after of obesity. A disease-specific test for diagnosis is not yet available . Neural crest tumors (ganglioneuroma, ganglioneuroblastoma) have been reported in 40% of patients. In our study, three patients diagnosed as having ROHHAD syndrome are presented from our hospital. In the evaluation of the hypothalamic functions of the patients, one patient had growth hormone deficiency and hyperprolactinemia; recurrent hypernatremia reflecting irregular water balance was detected in one patient. There was abnormal pupil reflex and heart rate irregularity in one patient; excessive sweating in one patient as autonomic dysfunction. In one patient, the diagnosis of paravertebral ganglioma accompanying ROHHAD syndrome was made. Non-invasive ventilation treatment was started in all patient because there was a sleep-disorder breathing clinic diagnosis. ROHHAD syndrome is a rare disease that requires a multidisciplinary approach because it includes complex symptoms and multiple organ system involvements. In these patients, should be sleep-disorder breathing determined early and appropriate treatment should be initiated immediately to reduce morbidity and mortality.